A Case with Seronegative Spondyloarthropathy: Ankylosing Spondylitis or Familial Mediterranean Fever? - Deniz Dülgeroğlu,; Canan Aybay,; Eylem D. G. Kırbıyık,; Ayşegül Barlak,; Sumru Özel, (Archives of Rheumatology, 2006)
Familial Mediterranean Fever (FMF) is an inherited genetic disease characterized with recurrent episodes of fever, and attacks of peritonitis, pleuritis, and synovitis. It is mostly seen in Sephardic Jews, Armenians, Turks, and Arabic races. In this case report, we present a Turkish male patient who had been followed for long years with the diagnosis of ankylosing spondylitis (AS), and then it was found that he had episodes of fever and abdominal pain and investigated for FMF in our clinic. This patient, who had spondylitis and bilateral sacroiliitis, was investigated both for AS and FMF. He was HLA B27 negative, and his findings were not fully consistent with AS except for sacroiliitis. There was no formation of syndesmophytosis, which is characteristic for AS. In the genetic analysis performed, M694V mutation was found in Mediterranean Fever gene that is frequently seen in FMF. As a result, it was concluded that the patient was a FMF case with SNSA. It was observed that fever and abdominal pain attacks were less frequent, and complaints of joints were better with Colchicine and nonsteroidal antiinflammatory drug regime. In patients with spondylitiis, sacroiliitis and involvoment of great peripheral joints fever and abdominal pain attacks must be inquired. If these are present and if the patient is from an ethnic origin consistent with FMF, then FMF must be considered, and the patient must be investigated also for FMF along with AS. (Rheumatism 2006; 21: 76-9)